SOUNDS OF MOLECULAR BIOLOGY - Blow, Nathan (BioTechniques, 2016)
Engineers and biologists are using sound to mix fluids, move cells, and dispense liquids. Nathan Blow looks at how acoustic science is changing molecular biology and high-throughput screening